Penguatan Karakter Siswa SIKL Melalui Modul P4 Untuk Internalisasi Nilai Pancasila - Rendi Prayuda; Rijalul Fikri; Aryo Akbar; Luis Guinando (Universitas Muhammadiyah Malang, 2026)
Purpose – This community service activity aims to strengthen the internalization of Pancasila values among students at the Indonesian School in Kuala Lumpur (SIKL) through the implementation of the Pancasila Appreciation and Practice (P4) Guidelines Module, which has been adapted to the characteristics of students in the Indonesian diaspora. This program was implemented as a solution to our partners’ need to strengthen national character amid the challenges of a multicultural environment and the dynamics of dual identity faced by the students. Design/methodology/approach – Activities included participatory workshops for teachers and students, reflective dialogue sessions, reinforcement of school culture and national symbols, and the production of digital learning media. Monitoring and evaluation used document review, observation of learning and routines, brief interviews, and simple pre-post assessments. Findings – The program increased student engagement and helped students articulate and practice Pancasila in daily behavior, including tolerance, deliberation, and mutual help. Implementation benefited from curriculum integration but faced challenges from global digital culture, the dominant Malaysian social environment outside school, and dual identity dynamics. Originality/value – This study proposes a model for strengthening national values among Indonesia’s young diaspora generation.